(untitled) (Al-Mansour Journal, 2023)
This study presents an experimental investigation of the expansive soil behaviour before and after treatment. To represent the behaviour of expansive soil, a mixture between natural soil and bentonite of 1:1 was adopted. A synthetic plaster was used to improve the geotechnical properties of the tested soil. It is normally used as an adhesive for pasting tiles. A series of tests were conducted for original soil and soil-additive mixtures to detect the effect and efficiency of synthetic plaster on the geotechnical properties of the soil. Different contents of (0, 2.5, 5.0, 7.5, 10.0) % by dry unit weight of soil were used. Compaction, Atterberge limits and swelling potential tests were conducted for untreated and treated soil. The results show that considerable decrease in plasticity index for treated soil compared with the original soil. The maximum dry density increased with increasing the additive contents up to 5.0 % and then decreased. In contrast, the optimum moisture content experienced decreased up to additive content of 5.0 % and then increased. A significant reduction in swelling potential from 170 % to reach 68 % for treated soil by 10% additive. Moreover, the swelling pressure shows a reduction from 143 kPa for untreated soil to a value of 84 kPa for the same previous soil mixture.